Influence of polyelectrolytes on increasing sensitivity of an immunofluorescent analysis based on plasmon silver nanoparticles - Koktysh, Irina V.; Mel’nikova, Yanina I.; Kulakovich, Olga S.; Ramanenka, Andrei A.; Maskevich, Sergey A. (Experimental Biology and Biotechnology, 2021)
It was studied the dependence of the interaction of the components of the immunofluorescence test system for the quantitative determination of prostate specific antigen based on plasmon silver nanoparticles on the physicochemical nature of various polyelectrolytes used to coat films of silver nanoparticles. It has been shown that the use of a weakly charged polycationic polyelectrolyte poly-L-lysine can increase the antigenic binding of the test system by 2.34 times, and the use of a highly charged polycationic polyelectrolyte polydiallyldimethylammonium chloride increases the binding affinity of prostatic specific antigen by 5 times. When developing various immunochemical test systems using films of silver nanoparticles, an important parameter is the choice of a polyelectrolyte for coating a silver nanolayer, since the physicochemical and electrostatic properties of the polyelectrolyte can significantly affect both the sorption capacity of the solid phase and the conformational state functional activity of immobilized protein molecules. Both specificity and sensitivity of the immunochemical test system, as well as the minimum possible detectable concentration of bioanalyte, largely depend on these parameters.
Keywords: fluorescence immunological analysis; polyelectrolytes; poly-L-lysine; polydiallyldimethylammonium chloride; fluorescein isothiocyanate; fluorescence; silver nanoparticles; plasmonics; prostate-specific antigen